Reflections on the Universal Declaration of Human Rights : a fiftieth anniversary anthology - Cornia, Giovanni Andrea; Danziger, Sheldon (The Hague : Kluwer Law International, 1998)
BMLIK
Engels
Monografie
Keywords: mensenrechten